Nilai Pendidikan dalam Novel Surat Kecil untuk Tuhan Karya Agnes Davonar - Dina Silvia Dina; Yayan Carlian; Alvin Yanuar Rahman (Al - Azkiya : Jurnal Ilmiah Pendidikan MI/SD, 2020)
This research is motivated by moral degeneration in early childhood. So it needs to be instilled in children about good morals from an early age, through learning akidah morals at MI, children can know, understand and apply them to their daily life. This writing is a qualitative descriptive analysis. Data collection techniques using documentation. Data analysis used Miles and Huberman's model. The conclusion of the discussion results contained in the novel Surat Kecil Untuk Tuhan, namely 1) morals towards Allah SWT includes faith, gratitude, prayer, tawakal, and obedience. 2) morals towards fellow humans, including a) morals towards oneself, namely responsibility, patience, sincerity. b) morals towards family, namely respect, affection and friendship. c) morals towards the community, such as friends, that is, please help. d) morality towards neighbours, that is, please help. 3) morals towards nature or the environment, namely admiring His creations and protecting the environment. The relevance of the values of moral education contained in the novel Surat Kecil Untuk Tuhan by Agnes Davonar with learning akidah akhlak in MI is that these values are included in the material of akidah akhlak in MI, and this novel can be used as a supporting medium in learning Akidah Akhlak at MI